(untitled) (Socio-economic relations in the digital society, 2019)
Under competitive conditions diagnosis of changes in the structure of income of an individual bank and the banking system as a whole is necessary for all participants in the economic process. The main share in the structure of the bank’s income is interest income. Therefore, for an eff ective management policies is important to know, as in the current period in the banking system are correlated the volume of obtained interest income and other indicators of banking activities. In Article The possibility of using the production function for diagnostics of structural dependencies of banking factors. Their impacts on the efficiency of the banking business are evaluated. This will allow diagnose those directions of banking business, that have a dominant influence to interest income, and to quantify the contribution of each source of formation of interest income.